Los militares y la modernización del Perú - Petras, James F.; Rimensnyder, Nelson (Estudios Internacionales, 1970)
Aware of the historical process that produced the current social structure and of the obstacles to industrial development, the Peruvian military regime has come to the conclusion that traditional political institutions are incapable of carrying out the necessary changes. That is why they have promulgated a broad program that includes important changes in the land tenure system and in the definition of sectors to which both public and private investment must be channeled. The Twenty-Year Plan, known as Peru’s long-term strategy for national development, reflects the greatest concern of the military government: rapid industrial development and social reforms.